Effect of Soil Conditioner on Carrot Growth and Soil Fertility Status - Ayer, Dipendra Kumar; Aryal, Sheetal; Adhikari, Keshav Raj; Dhakal, Krishna; Sharma, Anupama (Journal of Nepal Agricultural Research Council, 2019)
A field experiment was conducted in popular carrot cultivar Nepa Dream using randomized complete block design (RCBD) with four replications for evaluating the effects of ten different treatments of soil conditioner in combination with organic and inorganic fertilizers on root growth and soil productivity. Soil samples from each microplot were also analyzed for soil texture, pH, organic matter, total nitrogen, available nitrogen, total phosphorus and total potassium before sowing and after harvest. Effects on soil was not significant in the single season experiment but effects of the treatments on the carrot root growth and production was significant. For higher root yield and biological yield, treatments Soil Conditioner +Micronutrient (Double Dose)+1/2 Recommended Dose of Fertilizer +1/2 Farm Yard Manure (T10) followed by Soil Conditioner +Micronutrient (Normal)+1/2Recommended Dose of Fertilizer +1/2 Farm Yard Manure (T7), and Recommended Dose of Fertilizer Full (T2) were found better whereas treatment T10 was found closer to T2 and Soil Conditioner +Micronutrient (Double Dose)+Farm Yard Manure Full (T9) which showed higher mean performances for root diameter, cortex diameter and root length of carrot. In contrast, total soluble sugar as % brix was found less in the treatments involving one or more combinations of conditioner whereas highest for Farm Yard Manure and Recommended Dose of Fertilizer treatments either alone or in combination. Thus, use of normal dose of GMT™ soil conditioner along with ½ Recommended Dose of Fertilizer and ½ Farm Yard Manure (T7) can be used as an alternative to T2 for higher carrot production which also can reduce the use of commercial inorganic fertilizers for improving soil fertility status. For organic carrot production at low cost, T9 can also be used as an alternative to other combinations of chemical fertilizers.